2021
DOI: 10.1128/jb.00659-20
|View full text |Cite
|
Sign up to set email alerts
|

TusA Is a Versatile Protein That Links Translation Efficiency to Cell Division in Escherichia coli

Abstract: To enable accurate and efficient translation, sulfur modifications are introduced posttranscriptionally into nucleosides in tRNAs. The biosynthesis of tRNA sulfur modifications involves unique sulfur trafficking systems for the incorporation of sulfur atoms in different nucleosides of tRNA. One of the proteins that is involved in inserting the sulfur for 5-methylaminomethyl-2-thiouridine (mnm5s2U34) modifications in tRNAs is the TusA protein. TusA, however, is a versatile protein that is also involved in numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In Escherichia coli , the three homologous TusA‐family proteins, TusA, YedF, and YeeD have distinct functions and cannot substitute for each other (Dahl et al, 2013 ). Besides contributing to tRNA thiolation (Ikeuchi et al, 2006 ), TusA mediates sulfur transfer for molybdenum cofactor biosynthesis and affects iron–sulfur cluster assembly as well as the activity of major regulatory proteins (Dahl et al, 2013 ; Ishii et al, 2000 ; Yildiz & Leimkühler, 2021 ). YeeD is a component of thiosulfate uptake for sulfur assimilation (Ikei et al, 2024 ; Tanaka et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Escherichia coli , the three homologous TusA‐family proteins, TusA, YedF, and YeeD have distinct functions and cannot substitute for each other (Dahl et al, 2013 ). Besides contributing to tRNA thiolation (Ikeuchi et al, 2006 ), TusA mediates sulfur transfer for molybdenum cofactor biosynthesis and affects iron–sulfur cluster assembly as well as the activity of major regulatory proteins (Dahl et al, 2013 ; Ishii et al, 2000 ; Yildiz & Leimkühler, 2021 ). YeeD is a component of thiosulfate uptake for sulfur assimilation (Ikei et al, 2024 ; Tanaka et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The defect of TusDCB may indirectly affect Fe-S biosynthesis, the other sulfur flow destination, by terminating sulfur flow to tRNA Lys , tRNA Glu and tRNA Gln . Another study showed that Tus proteins contribute to the expression of the global regulators RpoS and Fis 55 . Even though the target of TusDCB's sulfur transfer activity is confined to tRNAs, it is involved in the regulation of diverse physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…TusA, which is a sulfur-carrying protein that mediates the 2-thiouridine (S 2 U34) wobble-position tRNA modification (Ikeuchi et al, 2006), was shown to be important for the efficient translation of rpoS (Aubee et al, 2017). Another study biochemically confirmed the role of TusA by showing that absence of TusA resulted in decreased translation efficiency of rpoS, through loss of thiolation on Lys, Glu and Gln tRNAs (Yildiz and Leimkühler, 2021). Thus, tRNA modifications and encoding of ORFs with specific codon preference, especially leucine, provide another means of regulation of RpoS, by modulating translational efficiency.…”
Section: New Regulatory Mechanisms Contribute To Increased Network Co...mentioning
confidence: 98%